Structural alterations of the EGFR gene in glioblastoma samples as a prognostic factor and molecular target for therapy - V. O. Varachev; O. Yu. Susova; A. A. Mitrofanov; G. S. Krasnov; D. R. Naskhletashvili; Yu. I. Ammour; S. D. Bezhanova; N. V. Sevyan; E. V. Prozorenko; A. Kh. Bekyashev; T. V. Nasedkina (Успехи молекулярной онкологии)
Introduction. Epidermal growth factor receptor (EGFR) is a transmembrane protein of the receptor tyrosine kinase family that is activated in various cancers (non-small cell lung cancer, colorectal cancer, head and neck tumors). In glial brain tumors, increased EGFR expression levels are characteristic of the most aggressive subtype, glioblastoma. Frequent structural changes of EGFR in glioblastoma are amplification of the chromosome region where the EGFR gene is located, point mutations, as well as deletion of exons 2–7 of the EGFR gene leading to the formation of EGFRvIII transcript.Aim. To determine structural changes of the EGFR gene (point mutations and amplification of the EGFR gene, EGFRvIII transcript) in tumor samples using different methods and to evaluate their potential clinical significance.Materials and methods. The study included 75 patients with brain gliomas (70 of them glioblastoma) aged 34 to 78 years (mean age 56 years). DNA and RNA isolation was performed from fresh frozen tumor tissue, as well as from peripheral blood leukocytes. EGFR gene mutations were determined by next-generation sequencing (NGS), and β allele frequency (BAF) comparative analysis (normal-tumor) was performed to determine the copy number of chromosome 7 regions. Quantitative polymerase chain reaction was used to confirm the EGFR gene amplification in tumor samples, and reverse transcription-PCR was used to detect EGFRvIII variant.Results. The NGS method revealed 11/70 (16 %) mutations in coding regions of EGFR gene in glioblastoma samples, the EGFR gene amplification was detected in 26/70 (37 %) cases; no structural changes of the EGFR gene were detected in 5 glioma samples (astrocytoma, oligodendroglioma). All cases of EGFR gene amplification detected by NGS were confirmed by quantitative polymerase chain reaction. To search for EGFRvIII transcript, 31 tumor RNA samples were examined, of which EGFR amplification was present in 12 samples. EGFRvIII transcript was detected only in samples with EGFR gene amplification – 4/12 (33 %). To assess the clinical significance of structural gene alterations, the frequency of occurrence in primary and recurrent glioblastoma samples was compared.Conclusion. The NGS method allows to detect both point mutations and amplification of the EGFR gene. The EGFR gene amplification was associated with EGFRvIII mutation in 33 % of cases. No statistically significant differences in the frequency of structural changes in the EGFR gene between primary and relapsed glioblastomas were found.